Depression and depressive symptoms in physicians prior to the COVID-19 pandemic: a systematic review and meta-analysis - Dhaliwal, Shan; Fremont, Deena; Li, Wenshan; Myran, Daniel; Solmi, Marco; Tanuseputro, Peter; Wilson, Janet; Sood, Manish M (Frontiers in Psychiatry, 2025)
BackgroundMental health disorders, such as depression, can significantly impact a physician’s well-being and the quality of care they provide. We conducted a systematic review and meta-analysis to identify risk factors and to estimate the prevalence of depression and depressive symptoms in physicians prior to the COVID-19 pandemic.MethodsThis PRISMA 2020–compliant systematic review and meta-analysis searched EMBASE, APA PsycINFO, and MEDLINE databases for studies published between January 2002 and March 2020 (pre–COVID-19 period). Risk of bias was assessed using a modified Newcastle-Ottawa Scale for cohort and cross-sectional studies. We included studies of physicians where depression/depressive symptoms were measured by either a validated questionnaire or clinical diagnosis. The primary and secondary outcomes measures included assessing the prevalence of depression/depressive symptoms, and whether depression differed by pertinent risk factors (study design, sex, specialty, training stage) in the literature prior to the COVID-19 pandemic.ResultsForty-two studies from 14 countries involving 27,284 physicians (7,293 with depression or depressive symptoms) were included. The pooled prevalence estimate was 34.2% (95% CI: 26.4-43.0%), with substantial heterogeneity identified across studies (I2 = 98%). Most studies were cross-sectional surveys (n=28) and cohort studies (n=14). A total of 13 different assessment methods were used. We found no statistically significant difference in depression between male and female physicians (OR: 0.78, 95% CI: 0.46, 131), and a slightly increased rates in residents compared to staff physicians [pooled estimates of 36% (95% CI: 26-47%) and 29% (95% CI: 13-53%)]. Finally, 25 studies were deemed “High” risk of bias, while the remaining 17 were “Low” risk.ConclusionsIn this review examining depression and depressive symptoms among physicians, we report a pooled estimate of 34% prior to the COVID-19 pandemic. Due to the high degree of heterogeneity in study design and limited examination of key risk factors, limited conclusions can be made regarding the true prevalence across the physicians, and how best to target interventions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021232814.